Rokeya’s anti-colonial ideas: corporate exploitation of women in Bangladesh - Hasan, Md. Mahmudul (2015)
ROKEYA Sakhawat Hossain (1880–1932) did not maintain any sense of hostility or prejudice against any particular group of people. Despite the fact that European colonisers were ravaging her country politically, economically and culturally, she did not demonstrate any anti-west bias in her work. She was targeting high. She was working persistently to create awareness of gender inequity and to equip her society so that it could get rid of the colonial yoke. The best way to decolonise India was, in her opinion, to establish gender justice in society so that both men and women could feel equally empowered to take part in a meaningful anti-colonial struggle. In literary discussion, however, her anti-colonial ideas are not adequately highlighted. Most women have broken the wall of seclusion which was impregnable and impermeable during Rokeya’s time. However, even though women have been able to participate in public life and enjoy employment opportunities, they are still placed in a subordinate role and receive unequal treatment and harassment. Women, whether at home or at workplace, have continued to encounter many gender discrepancies and discrimination. In the twenty-first-century Bangladesh, many women are waging a continuous battle to earn their agency and to appear and participate in public life with honour and dignity. In their continuous struggle, Rokeya still remains a beacon of guidance.